HISTORICAL ANALYSIS OF THE FORMATION OF INBOUND TOURISM IN UZBEKISTAN - Матхолиқов Қ. А. (TARIXIY TADQIQOTLAR, 2025)
This article analyzes the early stages of the formation of the tourism system in Uzbekistan based on archival sources. The study examines the emergence of tourism in a proletarian direction within the framework of the economic and cultural policies implemented during the first decade of Soviet rule, highlighting its ideological and organizational features. Furthermore, the article explores the establishment of the first tourism organizations in the country, the creation of tourist bases, and their activities. The organizational structure of tourism and its existing problems are studied on the basis of archival documents, leading to relevant conclusions.